LIFE SKILLS AND EDUCATIONAL ADJUSTMENT AMONG ADOLESCENTS-A STUDY - Dr.Sarla; Ms. Rekha; Ms. Annu (EPRA International Journal of Research and Development (IJRD), 2022)
The present study was investigated relationship the Life skills and educational adjustment among adolescents’ students Sonipat District. Descriptive survey method was used. The tools for data collection in scale on life skills standardized by Nair A.R.K. Subasree R& Ranjan Sunitha (2010) and Educational Adjustment standardized by Seema Rani and Dr. Basant Bahadur Singh. Data was analyzed using mean, mode,median, sd,t-test.The findings of the research is that there is no significant difference between Boys & Girls,Govt. & Private and Rural & urban students. Life skills & Educational Adjustment is the important part of life. It help individual need and help better life and dealing with issues as student life skills improvement and building citizen.